Машиностроительное черчение. Разрезы и сечения на чертежах - Малышев Александр Сергеевич (1963)
Экземпляры: КХ (20240625) / Инвентарный номер: 0139197 / Сис.шифр: 6.07 / Авт.знак: М 20 / ГРНТИ: 55 / ББК: 3